Analysis of dynamic behavior of direct current motor with electrical braking techniques - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, we examine simulation models of shunt, separately excited and permanent magnet direct current motor dynamic behavior during starting, steady state and stopping time (electrical braking) for dynamic simulation of electromechanical energy conversion using MATHEMATICA 10 environment. It is surly important to control the speed; keep it constant and reduce it safely with desired time while the direct current motor is fulfilling the requested torque. Therefore, we designed a complete direct current motor operation system and analyzed its performance by using MATHEMATICA 10 Software. In order to simulate the direct current motor, three types of identical motor parameters such as separately excited, shunt, and permanent magnet, based on the catalogue values, are constructed. © 2017 IEEE.
Keywords: Brakes; Dynamic Behavior; MATHEMATICA; PMDC motor; Separately Excited DC Motor; Shunt Excited DC Motor